Solar powered electrocoagulation processes for PB(II) removal using novel electrode materials and configurations / Farihahusnah Hussin - Farihahusnah , Hussin (2018)
Electrocoagulation is a process used to remove heavy metals from diluted wastewater streams using anode materials such as aluminium, iron and copper. One of the disadvantages of conventional electrocoagulation systems is the high operating costs associated with the high energy consumption of these systems. However, nowadays, it is possible to develop a solar photovoltaic electrocoagulation system with the advent of renewable energy technologies. This study is divided into four parts. In Part 1, a new material (perforated zinc) was proposed for the anode of the solar photovoltaic electrocoagulation system to remove lead (Pb(II)) ions from aqueous solutions. The effects of the type of electrode material, electrode geometry, energy consumption and sludge production on removal of Pb(II) were also investigated in this study. Part 2 of this study evaluates the effect of operating parameters such as electrode distance, pH, current density and initial concentration on Pb(II) removal efficiency of solar photovoltaic electrocoagulation. The results showed that the perforated zinc electrode gives superior performance with a Pb(II) removal efficiency of 99.9% after 10 min of treatment at a current density of 1.13 mA/cm2. Morphological and elemental analyses were carried out on the electrode surface and the formed sludge in which the results confirmed that a lower amount of sludge was produced during the removal of Pb(II) from the simulated wastewater using the solar photovoltaic electrocoagulation system under optimal conditions. Part 3 of this study involves the assessment on the feasibility of oil palm shell activated carbon (OPSAC) as an adsorbent for removal of Pb(II) ions from aqueous solutions. Batch experiments were conducted by varying the initial Pb(II) concentration, pH, treatment time, temperature and adsorbent dosage for the adsorption process. The structure and surface texture of the prepared materials were characterised using FESEM, EDAX and BET surface area analysis. The results indicated that the adsorption process achieved equilibrium after 30 min of treatment. In addition, the adsorption of Pb(II) is strongly dependent on pH, whereby the highest Pb(II) removal was attained at pH 6. The Pb(II) removal efficiency increases with an increase in the OPSAC dosage of up to 4 g/L and the highest Pb(II) removal efficiency achieved was 99.1%. The results suggest that the adsorption data are well-described by the Langmuir isotherm model, whereby the maximum adsorption capacity is 58.05 mg/g. In addition, the adsorption kinetics are best described by the pseudo second-order model. In Part 4 of this study, an integration system of electrocoagulation-activated carbon adsorption process was carried out to remove Pb(II) ions from aqueous solutions. The optimum results obtained from the electrocoagulation and adsorption studies were used to investigate the performance of this integration treatment by varying the pH, initial Pb(II) ion concentration and OPSAC dosage.